Hubungan Tingkat Kecemasan dengan Kualitas Tidur pada Pasien Gangguan Cemas (Ansietas) - Putri A, Filzah Az-zahrah; Sudayasa, I Putu; Eddy, Nur (NHM PRESS, 2021)
Sleep is something that everyone needs because it has a homeostatic function and plays an important role in thermoregulation and normal energy reserves. A person's sleep quality is influenced by various factors, one of which is psychiatric disorders. When feeling anxious, there is an increase in noradrenergic levels due to stimulation of the sympathetic nervous system and can reduce GABA (Gamma Amino-Butyric Acid) levels so that a person will find it difficult to initiate sleep. This study aims to analyze the relationship between anxiety levels and sleep quality in patients with anxiety disorders (anxiety) at the Muna Hospital. This research is an observational analytic study with a cross sectional design. The population of this study was new case patients diagnosed with anxiety disorders at the Muna Hospital in 2020. The sample was selected using a total sampling technique. The instruments used were the HARS (Hamilton Anxiety Rating Scale) questionnaire to measure anxiety levels and the PSQI (Pittsburgh Sleep Quality Index) questionnaire to assess sleep quality. Data analysis used the Spearman correlation test and the results of the analysis were declared significant if the p value = <0.05. Research shows that the level of anxiety is mild (20%), moderate anxiety (34%), severe anxiety (40%), very anxious (3%), good sleep quality (36%), and poor sleep quality (64%). The results of data analysis showed that there was a very close (r = 0,772) relationship (p = 0.001) between anxiety levels and sleep quality. There is a very close relationship between the level of anxiety and sleep quality in patients with anxiety disorders (anxiety) at the Muna Hospital.